Outcome of Calyceal Access with or Without Retrograde Pyelography in Percutaneous Nephrolithotomy (Bangladesh Journal of Urology, 2022)
Background: Percutaneous nephrolithotomy (PCNL) has gradually evolved to be one of the main endourologic treatment options for managing renal stone. For successful enctry into pelvicalyceal system can be obtained by fluoroscopy, ultrasonography and sometimes computed tomography (CT-guided) after RGP, but many are done without RGP. In this study, our objective was to compare the clinical outcomes of renal calculi management by PCNL with and without retrograde pyelography.Method: This quasi experimental study conducted on 60 cases with opaque renal calculi in lower, middle and upper calyx and lower calyx with renal pelvis. They were grouped into 2 groups purposely, one with RGP (30 patients) while other without RGP (30 patients).Result: We found no statistically significant difference between RGP and non RGP group in terms of duration of surgery (71.68 ±12.95 minutes vs 78.84±15.56 minutes), duration of radiation exposure (3.55± 1.34 min vs 3.74± 0.52 minutes) & hospital stay (3.0± 0.8 vs 2.6 ±1.0 days). Around 93.33 percent of the patients in the RGP group (n=28) were stone free, whereas in the Non-RGP group, 90% percent of the patients (n=27) were stone free.Conclusion: We can avoid RGP during PCNL in selected cases for pelvicalyceal access in the sight of no significant differences in duration of surgery, duration of radiation exposure, Hospital stay & complications in PCNL either with or without RGP.Bangladesh J. Urol. 2021; 24(1): 87-89